Land use change patterns and landscape ecological risk assessment in the process of watershed ecological compensation - Chen, Haitao; Ren, Jiaxue; Ren, Wenjing; Luan, Hui; Luo, Liancong (Frontiers in Environmental Science, 2025)
As China’s pioneering cross-provincial ecological compensation zone, the upper Xin’an River Basin harbors immense ecological value. However, the long-term effects of its compensation policies on land use dynamics and associated landscape ecological risks (LER) remain poorly understood. Leveraging Google Earth Engine (GEE), this study analyzes land use changes from 1990 to 2020 and develops an LER assessment model to characterize spatiotemporal risk patterns. The GeoDetector model is then employed to quantify the relative influence of four categories of driving factors on LER. The results reveal that: (1) Forests have consistently dominated the landscape, with notable expansions in forest, waterbody, and urban areas, while cropland and tea plantations have declined; key transitions include bidirectional conversion between forests and tea plantations, as well as cropland conversion to other land uses; (2) The overall LER in the watershed has generally declined, particularly during the ecological compensation period, underscoring the policy’s positive impact. Spatially, LER exhibits distinct clustering patterns, with high-risk areas concentrated near urban centers and low-risk zones prevailing in mountainous regions; and (3) Natural factors, especially elevation and temperature, are the dominant drivers of LER patterns, while socioeconomic and accessibility factors have a limited impact. Collectively, these findings reflect the interplay between urbanization and ecological conservation efforts, offering a scientific foundation for optimizing watershed management under ecological compensation frameworks.